Verification of a formula developed to predict the postoperative intraocular pressure after cataract surgery in primary angle‐closure glaucoma. Issue 12 (December 2016) - Chang, Yu‐Fan; Ko, Yu‐Chieh; Lau, Ling‐Ing; Liu, Catherine Jui‐Ling
Abstract : Background : The aim of this study was to verify the accuracy of a formula predicting postoperative intraocular pressure (IOP) after phacoemulsification and intraocular lens implantation (PHCE‐IOL) in primary angle‐closure glaucoma (PACG). In a retrospective chart review of patients with PACG who underwent PHCE‐IOL between 2011 and 2014, we collected preoperative IOP, axial length, anterior chamber depth (ACD), number of pre‐PHCE glaucoma medications, and IOP and glaucoma medications at 1 month and 3 months post‐PHCE. Methods : Post‐PHCE IOP values at 1 month and 3 months were compared with those predicted using the formula: postoperative IOP = 6.354 + 0.186 pre‐PHCE IOP × pre‐PHCE ACD. Agreements between measured and predicted IOP values were analyzed using correlation coefficients and Bland–Altman plots. Results : Of the 62 eyes included, the average pre‐PHCE IOP was 19.47 ± 5.84 mm Hg. Post‐PHCE IOP values were 14.94 ± 4.03 mm Hg at 1 month and 14.21 ± 3.51 mm Hg at 3 months. Patients using more preoperative medications tended to show greater postoperative declines in medication usage. Predicted IOP significantly correlated with post‐PHCE IOP measured at 1 month ( R = 0.314, p = 0.013) and 3 months ( R = 0.325, p = 0.01). Bland–Altman plots of difference against average of measured and estimated IOP revealed two cases falling outside ± 1.96 standard deviation at 1 month, and five cases at 3 months, indicating good consistency between measurement and prediction. Conclusion : This formula was useful for predicting IOP at 1 month and 3 months after PHCE‐IOL in PACG. It aids clinicians in preoperative assessment of whether PHCE‐IOL alone is likely to achieve acceptable postoperative IOP control.